Synthesis and characterization of biochar from peel and seed of jackfruit plant waste for the adsorption of copper metal ion from water - Mohammed Kadhem Abid (Tanjong Malim, 2019)
Synthesis and characterization of biochar from peel and seed of jackfruit plant waste for the adsorption of copper metal ion from water by Mohammed Kadhem Abid